Cognition and Functional Recovery in Severe Mental Disorders-A Narrative Review - J Jane Rinita; Suvarna Jyothi Kantipudi (Journal of Clinical and Diagnostic Research, 2023)
Severe Mental Illness (SMI) like schizophrenia and mood disorders has a prolonged and strenuous course which takes a major toll on the lives of the patients. In an effort to understand the consequence of these illness functional recovery has been studied in detail in the past. Cognitive impairment has been identified as an important contributor to the functional recovery. Cognitive impairment is an important component, independent of the symptoms, of SMI. Various cognitive deficits are found to occur in patients with SMI. Patients with lesser cognitive deficits were found to have better outcomes. This narrative review explains about cognitive impairment and functional outcome in people with SMI and the existing evidence for the relationship between both. Authors had performed manual search strategy of PubMed, Google Scholar engines for relevant research publications and reviewed them along with cross references from the retrieved articles. A broad review on the research shows, cognitive impairment has been recognised in both patients with schizophrenia and bipolar disorder even during periods of symptomatic remission and that people with symptomatic recovery continued to have functional deficits. This review also showed that patient with lesser cognitive deficits had better outcomes. Keeping this in mind, cognitive rehabilitation should be made a part of the management of SMI to achieve complete functional recovery.